Plano de texto e sequências textuais em problemas matemáticos e algumas considerações acerca da leitura desses textos - Veronese, Isabele (2015)
Considering that is common toal location of students' difficulties in solving problems to the inability to read; there are studies that point to the relationship between reading and solve problems, and the formation of problems player requires specific strategies to approach these texts in the classroom, we aim in this research was to analyze the text plan and textual sequences of math problems to verify the predominant text marks in these texts that can contribute tothe development of reading strategies appropriate to these texts.Therefore, based on Adam's studies (2004, 2011), Marquesi (2004 ) and Travaglia (1991, 2007) on text plan, textual sequences and text types, we analyzed tenmath problems proposed for students from 5th grade of elementary school in Five text books of great national movement, namely: 1) A conquista da Matemática, da editora FTD; 2) Matemática Pode contar comigo, da editora FTD; 3) Saber Matemática, da editora FTD; 4) Projeto Buriti Matemática, da editora Moderna; 5) Asas para voar Matemática, da editora Ática. Based on these analyzes, we discuss the regular text marks and high light text plan and textual sequences present in the texts of math problems